Prostaglandin F2α Facilitates Platelet Activation by Acting on Prostaglandin E2 Receptor Subtype EP3 and Thromboxane A2 Receptor TP in Mice - Kashiwagi, Hitoshi; Yuhki, Koh-ichi; Imamichi, Yoshitaka; Kojima, Fumiaki; Kumei, Shima; Tasaki, Yoshikazu; Narumiya, Shuh; Ushikubi, Fumitaka (Thrombosis and Haemostasis, 2019)
Platelets play an important role in both physiological hemostasis and pathological thrombosis. Thromboxane (TX) A2 and prostaglandin (PG) I2 are well known as a potent stimulator and an inhibitor of platelet function, respectively. Recently, PGE2 has also been reported to regulate platelet function via PGE2 receptor subtypes. However, the effect of PGF2α on platelet function remains to be determined. The aim of the present study was to clarify the effect of PGF2α on murine platelet function both in vitro and in vivo. Platelets prepared from wild-type mice (WT platelets) expressed several types of prostanoid receptors, including the PGE2 receptor subtype EP3 and the TXA2 receptor TP, while expression of the PGF2α receptor FP was not detected. In WT platelets, PGF2α potentiated adenosine diphosphate-induced aggregation in a concentration-dependent manner, while PGF2α alone did not induce aggregation. In platelets prepared from mice lacking FP, however, PGF2α-induced potentiation was not significantly different from that in WT platelets. Interestingly, the potentiation was significantly blunted in platelets lacking EP3 or TP and disappeared completely in platelets lacking both EP3 and TP. Accordingly, PGF2α decreased the cyclic adenosine monophosphate level via EP3 and increased the inositol triphosphate level via TP in WT platelets. Intravenously administered PGF2α significantly shortened the bleeding time and aggravated arachidonic acid-induced acute thromboembolism in WT mice, suggesting that PGF2α works as a platelet stimulator also in vivo. In conclusion, PGF2α potentiates platelet aggregation in vitro via EP3 and TP but not FP. Accordingly, PGF2α facilitates hemostasis and thromboembolism in vivo.
Keywords: platelet aggregation; prostaglandin F2α; EP3; TP